2005
DOI: 10.1111/j.0001-6349.2005.00881.x
|View full text |Cite
|
Sign up to set email alerts
|

Variables that predict the success of labor induction

Abstract: Cervical length, Bishop score, and parity predict the success of labor induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 12 publications
5
30
0
Order By: Relevance
“…2,[6][7][8][9] Induction of labour is most challenging in nulliparous women, 10 and the optimum technique for cervical ripening in this group is unknown. 11 The method most commonly used to identify readiness for onset of labour is the modified Bishop score which includes quantitative measures of consistency and dilation of the cervix, and station and position of the presenting part. 12 Originally developed to assess the likelihood of labour in multiparous women, it has since been applied to nulliparous women undergoing induction of labour.…”
Section: Introductionmentioning
confidence: 99%
“…2,[6][7][8][9] Induction of labour is most challenging in nulliparous women, 10 and the optimum technique for cervical ripening in this group is unknown. 11 The method most commonly used to identify readiness for onset of labour is the modified Bishop score which includes quantitative measures of consistency and dilation of the cervix, and station and position of the presenting part. 12 Originally developed to assess the likelihood of labour in multiparous women, it has since been applied to nulliparous women undergoing induction of labour.…”
Section: Introductionmentioning
confidence: 99%
“…With these components, the different studies produced new scores or algorithms, allowing one to divide patients into subgroups with different labor induction prognoses. [29][30][31][32][33][34][35][36] Although these models are more complex with several variables to be accounted for, their predictive values appear superior to any factor used alone.…”
Section: Predicting the Success Of Labor Inductionmentioning
confidence: 99%
“…In pregnant women undergoing induction of labor, successful vaginal delivery and the induction‐to‐delivery interval can be predicted by considering maternal characteristics, obstetric history and preinduction sonographic measurement of cervical length. However, a systematic review and meta‐analysis of 31 studies showed that cervical length at or near term contributes only moderately to predicting the outcome of delivery after induction of labor.…”
Section: Introductionmentioning
confidence: 99%